Fuzzy influence diagrams: An alternative approach to decision making under uncertainty - Mateou, Nicos; Hadjiprokopis, A. P.; Andreou, Andreas S. (My University, 2005)
This paper proposes a strategic management methodology using Influence Diagrams to represent and model decision problems. While Decision Trees have been extensively used for this purpose and are still highly useful, Fuzzy Influence Diagrams, a new representation for decision problems, outperform them in many respects. This paper describes influence diagrams, proposes their extension via fuzzy logic and demonstrates their use in crisis management and decision making. Simulation experiments using the proposed Fuzzy Influence Diagrams indicate specific conditions and constraints that enable political analysts and decision makers to set targets and plan their actions on a prediction basis. © 2005 IEEE.
Keywords: Mathematical modelsTrees (mathematics); Computer simulation; Constraint theory; Decision making